Mapeamento das informações arquivísticas e documentos arquivísticos produzidos pelo governo federal no contexto da pandemia de Covid-19 no Brasil - FEITOSA, Amanda Yvaloo Brasil (2023)
Exploratory research with a qualitative approach, combined with bibliographic research and documentary research, with the objective of mapping archival information and archival documents produced by the federal government in the context of the COVID-19 pandemic in Brazil. Identifying the incidence of disinformation processes from information and archival documents produced by the federal government, verifying how subjects appropriate, attribute values and disseminate this information. The research is justified by the relevance of the discussions that bring Archival Science closer to emerging themes such as Information Literacy, Critical Information Literacy and critical studies in general, considering that such studies are directed to social, historical, economic, political and cultural issues, essential elements when discussing access to information - focus of archival actions. Government archival information and documents can be configured as essential pieces in disinformation processes that are not only manifested through false information, they can be configured as distortions or parts of the truth, decontextualized, fragmented, manipulated information, removed from its historicity, biased, that erases reality, distorts, subtracts, labels or confuses (BRISOLA; BEZERRA, 2018, p. 3319). Given the current Brazilian and global political-economic scenario, the creation, distortion and dissemination of information can be observed, generally associated with the emergence and rise of leaders and groups with anti- democratic discourses. From this perspective, it is urgent to bring archival discussions closer to that of informational phenomena and alternatives that aim to minimize their potentially harmful effects in the context of the construction and preservation of informational heritage (FURTADO; SANTOS; SANTOS, 2022). Therefore, Information Literacy is relevant both for students and information professionals and for citizens to develop their learning and critical thinking in order to understand and interpret information, regardless of the context in which they are used.